1998
DOI: 10.1038/sj.cdd.4400414
|View full text |Cite
|
Sign up to set email alerts
|

Fas and Fas-mediated effects on a human salivary cell line in vitro: a model for immune-mediated exocrine damage in Sjögren's syndrome

Abstract: Sjo È gren's syndrome (SS) is an autoimmune exocrinopathy characterized by mononuclear cell infiltration and loss of parenchymal tissue in salivary and lacrimal glands. The mechanisms for these histologic alterations are not known. Apoptotic cell death, induced by the ligation of Fas (APO-1/ CD95) with Fas ligand (FasL/CD95L) may be an explanation for the tissue damage seen in SS. Fas and FasL were detected in minor salivary glands from SS patients and healthy individuals using immunohistochemical methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Several studies have indicated that IFN-increases the sensitivity to anti-Fas mAb, likely through the upregulation of Fas receptor expression [13,26,39]. As already mentioned, the co-existence of Fas and FasL on the surface of certain types of epithelial cells has been shown to result in suicidal or fratricide death [24,25].…”
Section: Participation Of the Fas Pathway In Sgec Apoptosis Induced Bmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have indicated that IFN-increases the sensitivity to anti-Fas mAb, likely through the upregulation of Fas receptor expression [13,26,39]. As already mentioned, the co-existence of Fas and FasL on the surface of certain types of epithelial cells has been shown to result in suicidal or fratricide death [24,25].…”
Section: Participation Of the Fas Pathway In Sgec Apoptosis Induced Bmentioning
confidence: 98%
“…Fas pathway has been previously shown to have an important role in the apoptotic cell death that is observed after treatment of various epithelial cells with IFN- [13,14,30]. Several studies have indicated that IFN-increases the sensitivity to anti-Fas mAb, likely through the upregulation of Fas receptor expression [13,26,39].…”
Section: Participation Of the Fas Pathway In Sgec Apoptosis Induced Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interactions are mediated by hormones, growth factors, cytokines delivering the signals into specific gene responses regulating cell division, apoptosis, and histodifferentiation (Jaskoll and Melnick, 1999). Specific cytokines can have multiple roles in regulating genes that encode for MMPs (Mengshol et al ., 2000), genes that are involved in programmed cell death (Gannot et al ., 1998), genes that influence neuronal responses (Soliven and Wang, 1995;Lu et al ., 1997), and genes that modulate immune responses. Potentially, one of the interesting pathways controlling this response is the insulin-like growth factor (IGF) system and its binding proteins (IGFBP), where the genes are located on mouse chromosome 1.…”
Section: (A) Geneticcontrol Of Autoimmunity Innod Mice Andhumanpatientsmentioning
confidence: 99%
“…These include the upregulation of HLA-DR due to interferon-g 3,4 , Fas and Fas ligand (FasL) induction by CD4 T cells 5,6,7,8 , as well as changes in other intracellular markers such as aquaporin 9,10,11 and costimulatory cell-surface markers 12 . The paradox of these studies is that the initial steps of apoptosis (Fas and FasL) are expressed in SS biopsies, but the actual progression to apoptosis (i.e., DNA fragmentation) in situ is a rare event in the SS biopsy 13 .…”
mentioning
confidence: 99%